Teacher Educators’ Experiences of Integrating Digital Technologies in English Language Teaching (KMC Journal, 2024)
Incorporating digital technologies into English Language Teaching (ELT) has become an essential aspect for enhancing teaching and learning experiences. This hermeneutic phenomenological study explores the experiences of four university-level English language teacher educators in Darchula regarding integrating digital technologies into ELT. Utilising semi-structured interviews and thematic analysis guided by the DigCompEdu Framework, the research reveals the educators’ lived experiences with digital technology integration. The findings highlight how digital tools are employed to improve teaching and learning experiences, boost student engagement, enhance access to educational materials, and create dynamic and interactive learning environments. Despite these benefits, the study also underscores the need to address technical challenges and adopt a balanced approach to using online resources to maximize advantages while mitigating potential drawbacks. By providing teacher educators and policymakers in Nepal with insights into the significance of digital technologies and the potential of the DigCompEdu framework, this article aims to promote more effective integration of digital technologies in ELT classrooms.